The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/hed.24350
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal growth factor receptor 2/neu as a novel therapeutic target in sinonasal undifferentiated carcinoma

Abstract: Targeting HER2 may be a promising avenue for the development of novel therapies for SNUC. © 2016 Wiley Periodicals, Inc. Head Neck 38: E1926-E1934, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
3
15
0
2
Order By: Relevance
“…We also identi ed copy gains in ERBB2 in 3/5 samples (Fig. 2b) suggesting a potential role of ERBB2 function in a subset of SNUCs, which has been previously noted (18). Moreover, we also identi ed copy number losses in SMARC family genes (SMARCA1, SMARCA2, SMARCA5, SMARCB1, SMARCC1 and SMARCE1) in numerous samples consistent with previous reports of the recurrence of alterations to this gene family in SNUC (16).…”
Section: Survival Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…We also identi ed copy gains in ERBB2 in 3/5 samples (Fig. 2b) suggesting a potential role of ERBB2 function in a subset of SNUCs, which has been previously noted (18). Moreover, we also identi ed copy number losses in SMARC family genes (SMARCA1, SMARCA2, SMARCA5, SMARCB1, SMARCC1 and SMARCE1) in numerous samples consistent with previous reports of the recurrence of alterations to this gene family in SNUC (16).…”
Section: Survival Analysissupporting
confidence: 89%
“…The patient derived SNUC cell line, MDA8788-6, was generously provided by MD Anderson. Generation of this cell line was previously described by Takahashi et.al (18). Cells were cultured in a humidi ed incubator at 37 °C with 5% (vol/vol) CO2 in DMEM with 10% FBS, 1X Pen/Strep, 1X NEAA.…”
Section: Cell Linementioning
confidence: 99%
See 1 more Smart Citation
“…No HER2 overexpression was identified in the 11 SNUC cases examined, although it was reported in one study using an animal model. 55,56 SOX-2 amplification was shown in about one-third of SNUCs and other sinonasal cancers, such as SCC, and this may be associated with relapse after primary therapy. 57 There are also variable results regarding SNUC and HPV infection.…”
Section: Sinonasal Undifferentiated Carcinoma Example 7: Sinonasal Unmentioning
confidence: 99%
“…This could be due to prolonged incubation with lapatinib. Previous studies have shown decrease of growth factor expression in terms of relative protein expression following incubation with tyrosine kinase inhibitors [12,29].…”
Section: Discussionmentioning
confidence: 95%